2015
DOI: 10.1088/0022-3727/48/21/215003
|View full text |Cite
|
Sign up to set email alerts
|

Spin transport enhancement by controlling the Ag growth in lateral spin valves

Abstract: The role of the growth conditions in the spin transport properties of silver (Ag) have been studied by using lateral spin valve structures. By changing the deposition conditions of Ag from polycrystalline to epitaxial growth, we have observed a considerable enhancement of the spin diffusion length, from ! !" = 449 ± 30 to 823 ± 59 nm. This study shows that diminishing the grain boundary contribution to the spin relaxation mechanism is an effective way to improve the spin diffusion length in metallic nanostruct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…The results of the fitting are in good agreement with previous work using similar Cu thickness [8,11]. To extract such information, usually a series of devices with varying L are needed [8,10,11,12,14,17,18,24], while in the current approach, the relevant parameters can be extracted from a single device. Hanle measurements, which can be used to extract the same information using a single device [15], are very sensitive to device details and its liability has been recently put into question [30,31,32,33].…”
Section: Extraction Of Spin Diffusion Parameterssupporting
confidence: 83%
“…The results of the fitting are in good agreement with previous work using similar Cu thickness [8,11]. To extract such information, usually a series of devices with varying L are needed [8,10,11,12,14,17,18,24], while in the current approach, the relevant parameters can be extracted from a single device. Hanle measurements, which can be used to extract the same information using a single device [15], are very sensitive to device details and its liability has been recently put into question [30,31,32,33].…”
Section: Extraction Of Spin Diffusion Parameterssupporting
confidence: 83%
“…Secondary sputtering refers to a phenomenon in which substrate material particles are torn off due to the physical impact of the accelerated plasma ions and the particles are emitted at various angles with a wide angular distribution (Figure 5a). [76,[154][155][156][157] The angle of the particles deviating from the physical impact of the accelerated ions during the ion-bombardment process can be mainly controlled by the acceleration voltage intensity, the type (size) of the accelerated ions, the type of target material, and the angle of incidence. After fabricating the prepattern on the target substrate layer, if the ion-bombardment process is performed, the particles of bottom layer etched by the accelerated plasma ions are uniformly deposited on the side surface of prepattern ( Figure 5b).…”
Section: Principle Of Secondary Sputtering Lithographymentioning
confidence: 99%
“…Repeatable SSL showed that SSL can create precise and accurate multidirectional patterns including grids and connected Olympic-ring shaped cylinders from single line and single pillar pattern shaped master patterns by performing the additional SSL fabrication process at a specific angle on the already fabricated SSL patterns. [154] Figure 8a,c shows SEM images for fabrication of various 3D nanostructures with multifeature shapes (Figure 8a), multilayer (Figure 8b), and false-colored SEM images of multicomponent three-way grid patterns with three different materials (Figure 8c). In the center image of Figure 8a, highly precise, uniform, large concentric ring-shaped structures ≈15 nm wide were prepared from a microsized concentric PS nanostructures via the first SSL process.…”
Section: Complex Nanopatterningmentioning
confidence: 99%
“…A NiFe(20 nm)/Ag(2 nm) reference sample was also deposited under the same conditions. As the reported value of λ s for Ag is approximately 450 nm [28], we can confidently neglect spin attenuation effects in this reference sample. The samples were finally annealed in situ at 500 K for 1 h in vacuum.…”
Section: Methodsmentioning
confidence: 67%